Adsorption Of Rhodamine B Dye By Acacia Bark Powder (Acacia crassicarpa) - Mukhlis .; Lathifa Azury; Sela Andesti; T. Abu Hanifah; Sofia Anita; Itnawita Itnawita (Jurnal Kimia Fullerene, 2026)
Acacia bark powder (Acacia crassicarpa) is a biomass containing cellulose compounds as active sites for adsorption. This study aims to optimise the adsorption parameters of Rhodamine B by acacia bark powder. The method used in this study is batch adsorption. The adsorbent is prepared in powder form with a particle size of 100–200 mesh. SEM-EDS characterisation results showed a porous surface morphology of the adsorbent, dominated by carbon (C) and oxygen (O) elements. BET analysis revealed a specific surface area of 0.460 m²/g, pore volume of 4.361×10⁻³ cc/g, and pore diameter of 379.008 Å. FTIR results indicated the presence of functional groups N-H, -OH, C-H, C=O, C=C, and C-O. Optimal adsorption conditions were obtained at an adsorbent dose of 0.5 g, pH 2, contact time of 50 minutes, stirring speed of 200 rpm, adsorbate concentration of 40 mg/L, and temperature of 50°C, with an adsorption efficiency of 99.04% and adsorption capacity of 3.9326 mg/g. The results of this study indicate that Acacia crassicarpa bark powder has good performance in adsorbing Rhodamine B dye.